Penerapan Metode Fuzzy Analytical Hierarchy Process (F-AHP) Untuk Menentukan Besar Pinjaman Pada Koperasi - Fernando Parulian Saputra; Nurul Hidayat; Muhammad Tanzil Furqon (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
One of the functions of cooperative is to offer loans. Loan offer has own risks, some cases of bad loans cause disadvantage for the cooperative. The same problems also happen at KUD Tuwuh Sari. The causes occur when KUD Tuwuh Sari can not analyze the value can be loaned correctly. This research offers a solution to solve the problems, by creating a system that can help KUD Tuwuh Sari to analyze and determine the value of the loan. Fuzzy Analytical Hierarchy Process (F-AHP) method applied to the system because this method has proven can solve the multi-criteria decision making (MCDM) problems, who have subjective side. The calculation process of F-AHP required consistent pairwise comparison matrix between criteria, with CR value < 0,1. Testing is done by comparing the suitability of the system's decisions to cooperative's, using k-fold cross validation method. And from this test known that, system's decision has an average 86% of compatibility levels.